Loss of Müller cell glutamine synthetase immunoreactivity is associated with neuronal changes in late-stage retinal degeneration - Reynisson, Hallur; Kalloniatis, Michael; Fletcher, Erica L.; Shivdasani, Mohit N.; Nivison-Smith, Lisa (Frontiers in Neuroanatomy, 2023)
Introduction A hallmark of photoreceptor degenerations is progressive, aberrant remodeling of the surviving retinal neurons and glia following photoreceptor loss. The exact relationship between neurons and glia remodeling in this late stage of retinal degeneration, however, is unclear. This study assessed this by examining Müller cell dysfunction via glutamine synthetase immunoreactivity and its spatial association with retinal neuron subpopulations through various cell markers. Methods Aged Rd1 mice retinae (P150 – P536, n = minimum 5 per age) and control heterozygous rd1 mice retinae (P536, n = 5) were isolated, fixed and cryosectioned. Fluorescent immunolabeling of glutamine synthetase was performed and retinal areas quantified as having low glutamine synthetase immunoreactivity if proportion of labeled pixels in an area was less than two standard deviations of the mean of the total retina. Other Müller cell markers such as Sox9 and Glial fibrillary acidic protein along with neuronal cell markers Calbindin, Calretinin, recoverin, Protein kinase C-α, Glutamic acid decarboxylase 67, and Islet-1 were then quantified within areas of low and normal synthetase immunoreactivity. Results Glutamine synthetase immunoreactivity was lost as a function of age in the rd1 mouse retina (P150 – P536). Immunoreactivity of other Müller cell markers, however, were unaffected suggesting Müller cells were still present in these low glutamine synthetase immunoreactive regions. Glutamine synthetase immunoreactivity loss affected specific neuronal populations: Type 2, Type 8 cone, and rod bipolar cells, as well as AII amacrine cells based on reduced recoverin, protein kinase Ca and parvalbumin immunoreactivity, respectively. The number of cell nuclei within regions of low glutamine synthetase immunoreactivity was also reduced suggesting possible neuronal loss rather than reduced cell marker immunoreactivity. Conclusion These findings further support a strong interplay between glia-neuronal alterations in late-stage degeneration and highlight a need for future studies and consideration in intervention development.